Gender Relation and Mood Choices: a Systemic Functional Analysis of Amma Darko's The Housemaid - Koussouhon, Léonard; Akogbeto, Patrice; Allagbe, A. Ayodele (My University, 2015)
Abstract
Keywords: Gender; mood choices; systemic functional linguistics